Clinical Characteristics and Management of Steroid-Induced Glaucoma - Pattih Primasakti; Lucyana; Fitratul Ilahi; Hendriati (HM Publisher, 2025)
Background: Steroid-induced glaucoma (SIG) is a secondary glaucoma characterized by elevated intraocular pressure (IOP) due to steroid use. This study aimed to analyze the clinical characteristics and management of SIG patients at Dr. M. Djamil General Hospital Padang, Indonesia, from January 2019 to August 2023. Methods: A retrospective descriptive study was conducted using medical records of patients diagnosed with SIG. Data collected included age, gender, steroid type, route of administration, duration of use, IOP at diagnosis, underlying diseases, glaucoma stage, and treatment. Results: Seventeen patients were diagnosed with SIG. The majority were female (70.58%) and aged 4-39 years (58.83%). The most common underlying diseases were systemic lupus erythematosus (SLE) and allergic conjunctivitis (47%). Oral steroid administration was most frequent (76.4%), with a usage duration of 2-12 months in most cases (70.6%). IOP at diagnosis ranged from 22 to 31 mmHg in most patients (82.3% right eye, 64.7% left eye). Most patients presented with mild glaucoma (70.5%). Topical anti-glaucoma medications were the primary treatment (76.4%), with trabeculectomy performed in some cases (23.6%). Conclusion: SIG is a preventable condition. Early detection and appropriate management are crucial to prevent vision loss. The clinical characteristics identified in this study contribute to a better understanding of SIG in our population. Further research on the interplay of risk factors, genetics, and histopathology is needed to enhance our comprehension of SIG.